NON-STANDARD TASKS AS A MEANS OF ACTIVATION ACTIONS OF JUNIOR SCHOOLCHILDREN - Druz, Z.V.; Druz, B.H. (Pedagogy of Higher and Secondary Education, 2004)
The peculiarity of using the utraditional tasks to activate junior pupils studying in innovation teaching technology are examined in the article.